Management of Patients Symptomatically Unresponsive to Levothyroxine: Natural Desiccated Thyroid Extract or the Combination of Levothyroxine and Liothyronine? A Research Priority - Heald, Adrian; Livingston, Mark; Hughes, Dyfrig (Experimental and Clinical Endocrinology & Diabetes, 2019)
Around 5–10% of hypothyroid patients continue to experience profound and sometimes disabling symptoms, including fatigue, depression and impaired cognition, in spite of being adequately replaced biochemically. The use of the combination of levothyroxine and liothyronine and natural desiccated thyroid extract is controversial for reasons of costs, a lack of evidence of additional benefit over levothyroxine alone, and potential safety concerns. Clinical guidelines caution against the use of both, and advise that only in exceptional cases may a short trial be considered. Natural desiccated thyroid extract is not licensed for use in the UK. However, key deficiencies in the existing evidence-base together with improved understanding of the pharmacology of levothyroxine resistance, indicates that now is the right time for a definitive clinical trial to address this important area of uncertainty.
Keywords: Primary hypothyroidism; levothyroxine-liothyronine therapy; resistant; T3; liothyronine; natural desiccated thyroid extract